Pat Steir - silent secret waterfalls the Barnes series (Lévy Gorvy Gallery, 2019)
This fully illustrated catalogue celebrates 'Silent Secret Waterfalls: The Barnes Series', an installation of new paintings by Pat Steir at the Barnes Foundation in Philadelphia. The exhibition presented eleven black-and-white paintings that wrapped around the interior of the building's Annenberg Court. Published by the Barnes and Lévy Gorvy, this volume includes a statement by Steir entitled "Pictures of Light," which attests to her conception of painting as a poetic and philosophic endeavor, and an interview between Steir and the Barnes' director and president, Thomas Collins. This illuminating conversation touches on her formative friendships with fellow artist Agnes Martin, composer John Cage, and art historian Douglas Crimp, as well as her engagement with the city of Philadelphia throughout her life. Exhibition: The Barnes Foundation, Philadelphia, USA (12.01.-17.11.2019)